Simulasi Pompa Banjir Untuk Mengatasi Banjir Di Jalan Sei Masang Kota Dumai - Yusuf, Rozi; Siswanto, Siswanto; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Flood is a frequent disaster in Dumai City and become problems from year to year so that require special attention to handle this matter. This study tries to solve the problem by using a pump. Pumping method can be able to function with optimally, it is necessary to be given temporary pond reservoirs. The pump is used to help accelerate drainage water collected in ponds. Case study area observed is Sei Masang street. this study conducted a pumps simulation with ponds reservoirs by water balance method. The discharge had been calculated by Rational method and IDF curve by Mononobe method. Ponds reservoirs sized (65m x 65m x 2m) requires pumping capacity of 0,5 m3 / sec to handle the floodwaters. So a pump 0,5m3 / sec can be to pump of water from ponds reservoirs to the sea as channel waster.Keywords: flood, drainage system, pond reservoirs, pumps